Risk Assessment in Solitary Fibrous Tumor of the Uterine Corpus: Report of a Case and Systematic Review of the Literature. (April 2022) - Ardighieri, Laura; Palicelli, Andrea; Ferrari, Federico; Ragnoli, Monica; Ghini, Iacopo; Bugatti, Mattia; Bercich, Luisa; Sartori, Enrico; Odicino, Franco E.
Solitary fibrous tumor (SFT) is an uncommon fibroblastic tumor occurring preferentially in the pleura, with a variable clinical course. SFT can arise also in numerous extrathoracic sites and very rarely in the female genital tract, with only scarce reports of uterine SFT. We reported a new uterine SFT arising in a 45-year-old woman, and we performed a systematic review of SFT cases of the uterine corpus interrogating the electronic databases PubMed, Web of Science, and Scopus. We identified only 13 patients diagnosed with SFT of the uterine corpus, including our one. Complete clinical workout at disease presentation showed no evidence of extrauterine spread in all cases, except for 1 patient who presented with metastatic disease. Tumor recurrences/metastases occurred in a minority of the patients and were poorly related to clinicopathological risk factors and patients stratification based on different scoring systems. Since the long-term clinical behavior of uterine SFT is limited and poorly predictable, extended follow-up is recommended also for all cases arising in the uterine corpus.